La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 578/2011 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2011)
Ejemplar: Revista de la ESG. Año 89, no. 578 (may-ago 2011). 120 p.